UNDERSTANDING VERBAL HUMOR THROUGH IMPLICATURE AND ENTAILMENT IN THREADS COMMENT INTERACTIONS - Bela Ayu Permatasari; Salsabila Fitriyani; Muhammad Hanafi; Tatu Siti Rohbiah (IdeBahasa, 2026)
This research focuses on examining humor within online communication by investigating implicature and entailment found in comments on social media. The data were collected using a documentation technique by capturing screenshots of humorous comments on the Threads platform. The data were analyzed through implicature and entailment analysis using pragmatic and semantic perspectives. The results indicate that implicature is a key aspect in the understanding of humor, as the majority of comments depend on suggested meanings rather than direct statements. Conversely, entailment serves as an supporting component that creates logical connections but is frequently overshadowed by the interpretation based on context. Furthermore, the digital environment, including shared knowledge, informal language, and an engaging communication style, greatly impacts the way humor is created and perceived. Consequently, humor in social media serves not only as a source of amusement but also reflects the users’ pragmatic skills and inventive use of language.